Transmission of cocoa viruses by mealybugs (Homoptera: Pseudococcidae) - Roivainen, Osmo (Agricultural and Food Science, 1976)
Several mealybug species reacted positively towards light and high humidity. Planococcoides njalensis (Laing) had a thermopreferendum at 20-25°C. and 25-33° C. was optimum for reproduction with a partial fecundity of 92 nymphs per female. T ½ biol. of 32P in the species was 11.4—15.3 days. Food uptake from virus infected plants was positively related to the infectivity of P. njalensis with cocoa swollen shoot virus isolate 1A. Plant and mealybug radioactivity were positively correlated. Amount of honeydew excreted by the species and the radioactivity of the honeydew were positively correlated. Frequency distribution of 32P in P. njalensis after feeding on 32P-active seedlings or sucrose solution was similar. Radiation effects on infectivity of mealybugs were not detected at 30 µCi/ml of 32P in seedling culture solution. With CSSV 1A and P. njalensis, preliminary fasting increased the rate of settling down to feed, the food uptake and infectivity of mealybugs. Virus was transmitted more often from stems than leaves of source plants. Groups of seedlings of 29—54 days old were almost equally good sources of virus for mealybugs and availability varied more between individual source plants. Mealybugs removed their stylets from source plants in 240 seconds. The length of acquisition access time for maximum transmission was 48—72 hours. Virus was not acquired during short feeds of up to one hour. Virus was acquired from infected seedlings by mealybugs via a parafilm membrane. Acquisition of virus from liquid leaf extract was rare. Virus persisted in mealybugs up to 72—96 hours and loss of infectivity was exponential with a T 1/2 of 12—13 hours. Virus persisted in the mealybugs through postacquisition moulting. Mealybugs vere seemingly more efficient vectors after postacquisition feeding than fasting, Latent period of virus in the test plants was short and over 98 % of the test plants showed virus symptoms in three months. With different numbers of mealybugs on test plants during the inoculation feed, the infection rate was as expected. The use of mealybugs while testing virus resistant and tolerant cocoa is demonstrated. Location of feeding mealybugs on test beans did not influence the infection rate. Virus transmission by mealybugs was not affected by light or darkness. The food uptake was highest and virus was transmitted most often in 29—36°C. The transmission of CSSV isolate 1M or cocoa mottle leaf virus isolate 1C with P. njalensis as the vector, or CSSV 1A with Ferrisia virgata (Cockerell) was similar to that of CSSV 1A with P. njalensis as the vector. A formula is given to describe the increase of infectivity in mealybugs during acquisition feed.